PENGARUH STANDAR OPERASIONAL PROSEDUR, DESKRIPSI PEKERJAAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN UMUM DAERAH PASAR - Widiartana, Dewa Made; Sri Kasih, Ni Luh (Komunitas Manajemen Kompetitif, 2024)
This study aims to analyze the influence of Standard Operating Procedures, Job Description, and Work Discipline variables on Work Productivity variables using multiple regression methods. The analyzed data shows that the Standard Operating Procedure (X1) variable has a positive and significant influence on the dependent variable, with a 95% confidence interval that is fully positive (0.067 to 0.641). The Job Description variable (X2) has an influence that is not always positive but still significant, with a 95% confidence interval that includes negative values (-0.016 to 0.441). The Work Discipline variable (X3) also shows an influence that is not always positive but significant, with a 95% confidence interval that includes negative values (-0.111 to 0.425). The F test shows that the regression model as a whole is significant (F = 122.867, p-value = 0.000), which means that the Standard Operating Procedure, Job Description, and Work Discipline variables together have a significant influence on the Work Productivity variable.